INVESTIGATING THE RELATIONSHIP BETWEEN BLOOD KLOTHO LEVELS AND GLYCATED HEMOGLOBIN IN DIABETIC NEPHROPATHY PATIENTS - Botirova Nigina Akram qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Diabetic nephropathy (DN) remains a significant complication of diabetes mellitus, characterized by progressive kidney damage due to prolonged hyperglycemia. Glycated hemoglobin (HbA1c) serves as a key marker for long-term glycemic control in diabetic patients, representing the average blood glucose levels over the preceding 2-3 months. Higher HbA1c levels are associated with an increased risk of diabetic complications, including nephropathy.Recent research has highlighted Klotho, a protein with renoprotective properties, as a potential modulator of kidney health in DN. Klotho is primarily expressed in the kidneys and has anti-inflammatory, anti-fibrotic, and antioxidant effects, which may provide protection against the pathophysiological processes that damage renal function in diabetes. This study explores the relationship between blood Klotho levels and HbA1c in DN patients, aiming to determine how glycemic control correlates with Klotho concentrations and whether Klotho could serve as an indicator of kidney protection in these patients.